Sinonasal Glomangiopericytoma - A Case Report - Nadeem, Muhammad Sohaib; Ali, Ujala; Zeb, Adnan; Khan, Muhammad Yousaf (Pakistan Armed Forces Medical Journal, 2022)
Sinonasal glomangiopericytoma is a tumor showing similarities to a glomus tumor but is less aggressive with a low malignant potential. The treatment of choice is complete excision followed by a regular long-term surveillance. The role of adjuvant chemotherapy and radiation remains undetermined. Our patient was a 45-year-old man who presented with nasal obstruction. Endoscopic excision showed sinonasal glomangiopericytoma. No adjuvant treatment was offered and patient was advised active surveillance. Patient was on a regular three-monthly follow-up. There was no evidence of disease recurrence after one year.